Positive tourism in Africa - Mkono, Mucha (Muchazondida) (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"Positive Tourism in Africa provides a crucial counter-narrative to the prevailing colonial and reductionist perspective on Africa's tourism trajectory and future. It offers a uniquely optimistic outlook for tourism in Africa whilst acknowledging the many challenges that African countries continue to grapple with. By examining broad and localized empirical studies, conceptual frameworks, culturally centered paradigms, and innovative methodological approaches for African contexts, this book showcases the many facets of tourism in Africa that illustrate hope, resilience, growth, and survival. This volume explores themes such as community-based tourism, wildlife tourism, tourism governance and leadership, crisis recovery, regional integration, the role of indigenous knowledge, event tourism and the impact of smart technologies. It acknowledges the challenges and opportunities for growth that exist in these various contexts and explores how tourism creates value for the spectrum of its participants. Including a wide selection of contributions from diverse authors, many of them African, this book offers an Afro-centric interpretation of tourism phenomena. It will be of great interest to students, researchers and academics in the field of Tourism and African Studies, as well as Development Studies and Geography"--
Positive tourism in Africa : resisting Afro-pessimism -- The community-based natural resource management programme in southern Africa : promise or peril? The case of Botswana -- Land reform and the promotion of collaborative community-based ecotourism at Somkhanda game reserve, South Africa -- Understanding the relationships between protected areas, tourism and community livelihoods : a systems thinking approach -- How community-based tourism can survive in turbulent environments : the Mahenye campfire project, Zimbabwe -- The "Afro-positive turn" : undermining Afro-pessimism through Afro-positive digital counter-narratives -- Broadening Uganda's tourism product base through indigenous cultural resource utilisation -- Insight into Africa : wildlife tourism as educational transformation -- Building cultural resilience in community-based tourism : the case of Goo-Moremi, eastern Botswana -- Leveraging tourism in Kenya through indigenous knowledge -- Regional integration : a lever for positive tourism development in Africa? -- Tourism progress in the SADC region : post-colonial era milestones -- Tourism and economic wellbeing in Africa -- The positive interaction between tourism development and human development : evidence from Mauritius -- Tourism governance and organizational infrastructure in the East African community : a baseline analysis -- The contribution of the law to tourism : the case of Mauritius -- Crises, controversies, and the future Terrorism and tourism recovery cases : a study of Tunisia and Egypt -- The trophy hunting controversy : how hunters rationalise their pastime in social media -- Management of a mature destination : Kruger National Park, South Africa -- The future of tourism in Africa : optimism in a changing environment.
OCLC-licensed vendor bibliographic record.
Keywords: Tourism -- Africa; Tourism -- Social aspects -- Africa; BUSINESS & ECONOMICS / Industries / General; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism